2012
DOI: 10.1111/j.1574-6968.2011.02470.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic genomic DNA reduces the production of pro-inflammatory cytokine tumor necrosis factor-alpha

Abstract: The effect of Lactobacillus plantarum genomic DNA on lipopolysaccharide (LPS)-induced mitogen-activated protein kinase (MAPK) activation, nuclear factor-kappa B activation, and the expressions of tumor necrosis factor-alpha, interleukin-1 receptor-associated kinase M, and the pattern recognition receptor were examined. Pretreatment of p-gDNA inhibited the phosphorylation of MAPKs and nuclear factor-kappa B, and also inhibited LPS-induced TNF-α production in response to subsequent LPS stimulation. L. plantarum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…frailty (Claesson et al, 2012), sarcopenia (Rampelli et al, 2013), cognitive impairment and AD (Porter et al, 2000; Widner et al, 1999)) by reduced production of short-chain fatty acids (SCFAs) which have a powerful immunoregulatory activity (Shapiro et al, 2014). Probiotics have the potential to rebalance gut microbiota and modulate gut immune response inhibiting the NF-κB pathway (Kim et al, 2012). Our findings suggest a significant moderate to large effect size of probiotics supplementation on reduction of inflammatory biomarkers, but it should be considered that this result could be overestimated by a significant small-study effect, at least for IL-6 studies.…”
Section: Discussionmentioning
confidence: 99%
“…frailty (Claesson et al, 2012), sarcopenia (Rampelli et al, 2013), cognitive impairment and AD (Porter et al, 2000; Widner et al, 1999)) by reduced production of short-chain fatty acids (SCFAs) which have a powerful immunoregulatory activity (Shapiro et al, 2014). Probiotics have the potential to rebalance gut microbiota and modulate gut immune response inhibiting the NF-κB pathway (Kim et al, 2012). Our findings suggest a significant moderate to large effect size of probiotics supplementation on reduction of inflammatory biomarkers, but it should be considered that this result could be overestimated by a significant small-study effect, at least for IL-6 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have explored the immunomodulatory potential of Lactobacillus genomic DNA. Kim and colleagues [2012] reported that pretreatment of monocytic THP-1 cell line with L. plantarum gDNA inhibited production of TNFα in response to LPS. Likewise, Bouladoux and colleauges [2012] have identified unique immunosuppressive motifs enriched in the DNA of Lactobacillus species that inhibit activation of dendritic cells in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…However, p-gDNA inhibits LPS-induced TNF-α production by THP-1 cells. Furthermore, p-gDNA reduces the expression of TLR2, TLR4 and TLR9, which induces the activation of NF-ĸB through the LPS signaling pathway, leading to the upregulation of inflammatory cytokines [153,154]. Pretreatment of p-gDNA inhibited the phosphorylation of MAPKs and NF-ĸB, and also inhibited LPS-induced TNF-α production in subsequent LPS stimulation.…”
Section: Mechanisms Of Action Of Probioticsmentioning
confidence: 99%
“…Pretreatment of p-gDNA inhibited the phosphorylation of MAPKs and NF-ĸB, and also inhibited LPS-induced TNF-α production in subsequent LPS stimulation. In this regard, L. plantarum genomic DNA-mediated inhibition of signaling and TNF-α was accompanied by the suppression of TLR2, TLR4 and TLR9, as well as the induction of IL-1 receptor-associated kinase M (a negative regulator of TLR) [154]. …”
Section: Mechanisms Of Action Of Probioticsmentioning
confidence: 99%